Evaluation of the performance of Abbott Panbio™ COVID-19 antigen rapid diagnostic test for the detection of severe acute respiratory syndrome coronavirus 2 at Harar, Eastern Ethiopia - Teklemariam, Zelalem; Feleke, Dereje; Abdurahman, Abdusemed; Alemayehu, Astawus; Demissie, Abebaw; Tufa, Asefa; Sherefa, Nebiyu; Mohammed, Abdusemed; Brhane, Mussie; Bogale, Kasahun (Frontiers in Medicine, 2023)
Rapid Antigen tests can help rapid detection, effective isolation of symptomatic cases, and systematic tracing of close contacts. However, the reliability of rapid antigen tests must be validated before they can be used widely. A cross-sectional study was conducted among 236 COVID-19 suspected patients visiting four health institutions in Harari Regional state, Harar, Eastern Ethiopia from June-July 2021. Two Nasopharyngeal samples were also collected and processed by the Panbio™ Ag-RDT kit directly and RT-PCR. Data were analyzed using SPSS version 25.0. The Panbio tests has sensitivity of 77.5% (95% CI: 61.6% - 89.2%), specificity of 98.5% (95% CI: 95.6%- 99.7%), Positive Predictive Value of 91.2% (95% CI : 76.9 % - 96.9%), negative Predictive Value of 95.5% (95%CI: 92.3%-,97.4%) and Kappa=0.81, (95% CI: 0.7- 0.9.). The test has sensitivity of 94.4%, 100%, 100% and 90% in sample collected from patients with in the 1-5 days duration of COVID post on set symptoms, age group <=18 years old and cycle threshold (Ct) values of < 20 and source of contact from house hold respectively. The overall sensitivity of Panbio™ COVID-19 Ag Rapid Test Device is 77.5 %. The test has sensitivity >=90% in the sample collected from symptomatic patients in early clinical course, age of <=18 years old, low Ct-values, and had contact with COVID patients in the household. Therefore, this test can be used as a point of care testing for diagnosis of symptomatic patients with shorted clinical course and contact with patients in the households.